2008
DOI: 10.1097/01.sga.0000324112.63532.a2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Nurses' Participation in Clinical Research

Abstract: Clinical research is necessary for developing nursing's body of knowledge and improving the quality of gastroenterology nursing care. The support and participation of nursing staff are crucial to conducting interventional research. Identification of characteristics of nurses and their work settings that facilitate or impede participation in research is needed. The purpose of this descriptive correlational study was to examine the effect of personal and professional characteristics and attitudes about nursing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Because we need clinical research and the healthcare environment is unlikely to change, we need strategies for conducting research under less than ideal conditions (Jacobson, Warner, Fleming, & Schmidt, 2008;Miller, Johnson, Mackay, & Budz, 1997). Jacobson et al (2008) studied staff nurses' clinical research activities and found that monetary compensation was important, and it was useful to have at least one person, whose major responsibility was data collection, helping with the study.…”
Section: Obstacles To Staff Nurse Involvement In Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we need clinical research and the healthcare environment is unlikely to change, we need strategies for conducting research under less than ideal conditions (Jacobson, Warner, Fleming, & Schmidt, 2008;Miller, Johnson, Mackay, & Budz, 1997). Jacobson et al (2008) studied staff nurses' clinical research activities and found that monetary compensation was important, and it was useful to have at least one person, whose major responsibility was data collection, helping with the study.…”
Section: Obstacles To Staff Nurse Involvement In Researchmentioning
confidence: 99%
“…Jacobson et al (2008) studied staff nurses' clinical research activities and found that monetary compensation was important, and it was useful to have at least one person, whose major responsibility was data collection, helping with the study. We were unable to pay the nurses because they were already being paid by the hospital to do patient care, but we did have two researchers who helped get informed consent, collect data, reviewed data collection forms, and contacted patients to get missing data.…”
Section: Obstacles To Staff Nurse Involvement In Researchmentioning
confidence: 99%
“…1 Once the study design and methods have been determined, it is important to keep good communication with the research site pending funding approval and review by the institutional review board. They may be interested in the project to fulfill the requirement for role advancement or in being a research assistant for the study.…”
Section: Research Planningmentioning
confidence: 99%
“…1 The purpose of this article is to discuss the challenges and opportunities for nurse researchers to conduct clinical research on hospitalized infants in the NICU. Creating a more research friendly environment and overcoming the barriers within clinical units is a major challenge for successful research programs.…”
mentioning
confidence: 99%
“…To engage in evidence‐based practice, PHNs must be familiar with the research process to be able to expand and improve their practice. Participation in research can enhance nurses' ability to improve the quality of their own practice, although many report major challenges to using research in the practice setting . Collaborative research programs between academic nurses and nurses in clinical settings have helped to overcome barriers to incorporating research in practice .…”
Section: Introductionmentioning
confidence: 99%